Essential but expensive? The World Health Organization, access to medicines and human rights. Issue 2 (June 2019) - Syrett, Keith
Now widely accepted as a component of the international human rights framework, the concept of access to medicines nonetheless continues to generate controversial questions as to its scope and application. Through critical analysis of relevant documentary materials, this article seeks to explore the conjunction between human rights and the list of essential medicines compiled biennially by the World Health Organization in the particular context of the recent expansion of this list to embrace a number of very costly medical interventions. Such extension is intended to stimulate access in the long run, but the expense of such medicines may limit accessibility in the short term, as governments struggling to ensure the sustainability of health systems choose to allocate finite resources elsewhere. This article therefore examines the compatibility of limitations to access on grounds of unaffordability, with international human rights obligations. It focuses especially upon Article 12 of the International Covenant on Economic, Social and Cultural Rights but also considers other human rights which may be engaged.